2014
DOI: 10.2215/cjn.06690613
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low-Protein Supplemented Diets with Fetal Growth in Pregnant Women with CKD

Abstract: Background and objectives Women affected by CKD increasingly choose to get pregnant. Experience with lowprotein diets is limited. The aim of this study was to review results obtained from pregnant women with CKD on supplemented vegan-vegetarian low-protein diets.Design, setting, participants, & measurements This was a single-arm, open intervention study between 2000-2012 of a low-protein diet in pregnant patients with stages 3-5 CKD or severe proteinuria (.1 g/d in the first trimester or nephrotic at any time)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 47 publications
3
45
0
Order By: Relevance
“…The two groups were comparable for age, referral, eGFR, and hypertension, while baseline proteinuria was higher in the intervention group. Even in this case, the experimental dietary regimen was tolerated and more interestingly the incidence of SGA babies was significantly lower in the diet group, while during the long-term follow-up, the children did not present health or socialization problems [33]. A subsequent analysis that compared 36 on diet CKD pregnancies vs. 47 CKD control cases on unrestricted diet in a follow-up of 15 years, confirmed that the incidence of SGA and/or extremely preterm babies (<28th week) was significantly lower in on-diet mothers than in the controls, suggesting again a possible positive effect of a plant-diet in CKD subjects [34].…”
Section: Clinical Experiencesmentioning
confidence: 73%
“…The two groups were comparable for age, referral, eGFR, and hypertension, while baseline proteinuria was higher in the intervention group. Even in this case, the experimental dietary regimen was tolerated and more interestingly the incidence of SGA babies was significantly lower in the diet group, while during the long-term follow-up, the children did not present health or socialization problems [33]. A subsequent analysis that compared 36 on diet CKD pregnancies vs. 47 CKD control cases on unrestricted diet in a follow-up of 15 years, confirmed that the incidence of SGA and/or extremely preterm babies (<28th week) was significantly lower in on-diet mothers than in the controls, suggesting again a possible positive effect of a plant-diet in CKD subjects [34].…”
Section: Clinical Experiencesmentioning
confidence: 73%
“…Previous study has revealed that CRF is characterized by slowly progressive chronic renal interstitial fibrosis (RIF) and accompanied with increased oxidative stress (OS) that is already found in the early stage of renal disease [5]. Although a low protein diets is the effective treatment regimen for CRF, the side effects of this strategy cannot be ignored, such as a probable occurrence of proteinuria and functional impairment [6]. The underlying mechanisms and more effective therapies for CRF are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant patients, who are also prescribed an adapted LPD, as elsewhere described, are not included in the present analysis [27]. …”
Section: Methodsmentioning
confidence: 99%